An Interdisciplinary Examination of the Material Effects of Deceptive Sport Beverage Advertisements. Issue 1 (13th February 2023) - Brison, Natasha T.; Baker, Thomas A.; Byon, Kevin K.; Evans, Nathaniel J.
Abstract: Sport companies frequently make product claims in advertisements to influence consumer purchase decisions. Sport beverages, in particular, often tout health benefits and performance claims. Unfortunately, some sport beverage claims may be false or misleading, persuading consumers to erroneously purchase products due to incorrect information. The Federal Trade Commission (FTC) prohibits any deceptive advertising resulting in a material effect on the consumer. Consumer behaviorists, however, rarely consider the FTC's guidelines in measuring consumer deception. Therefore, drawing upon consumer behavior theory and the FTC's guidelines, this paper examines the material effects of deceptive sport beverage advertisements. The authors identify and define three types of materiality: cognitive, affective, and behavioral. Employing a within-subjects experimental design, two studies were conducted: print and Facebook. The results reveal both types of deceptive advertisements had positive and statistically significant effects on all three types of materiality. These findings substantiate the determination of a violation by the National Advertising Division (NAD) and support further investigation of deceptive sport beverage advertising and marketing practices by the FTC.